Evaluation of microinsurance distribution strategy at the bottom of the pyramid by Liberty Life Swaziland - Lukhele, Mlungisi Reginald (Rhodes University, Faculty of Commerce, Rhodes Business School, 2015)
This is a qualitative study which focuses on how Liberty Life Swaziland distributes microinsurance to the bottom of the pyramid within Swaziland. Using stratified purposive sampling, this study identified 5 managers within Liberty Life and 4 managers from brokerages and affinity partners who had a minimum of 3 years' experience in distribution of microinsurance. Semi-structured and in-depth interviews were conducted by the researcher with these managers. Interviews were stopped when there was data saturation. To induce emerging themes from the data, open-coding and constant comparison technique was used. Findings in this study reveal that to distribute microinsurance to low income households, Liberty Life objectives are to; (1) provide relevant solutions in a cost effective manner, thus keeping premiums as affordable as possible, (2) provide simple products which are easy to understand by customers, (3) make services accessible, and (4) make doing business easy. In this regard, Liberty Life distribution strategy is to partner with bulk retailing entities that have a client base they already service and benefit from nationwide presence and infrastructure. Lastly, the perspectives of both internal and external stakeholders in microinsurance are discussed to evaluate the challenges and successes experienced in implementing the distribution strategy. This study is valuable to critically understand the current distribution strategy from the viewpoint of key intermediaries, but also pinpoint how efforts to achieve microinsurance distribution objectives can be enhanced. Lastly, the study recommends that; a selection criteria be set for distribution partners, partnership with mobile network operators, investment in continuous training of distribution partners and knowledge sharing between Liberty and intermediaries to cease the opportunity at the bottom of the pyramid.
Keywords: Uncatalogued